The Effect of Technology Acceptance Model (TAM) on Trust toward GrabFood Dine-Out Deals Feature from Generation Z Perspective in Indonesia - Maria Siregar (MINOVa Ditria Jaya, 2025)
Digital transformation has significantly reshaped consumer behavior, particularly among Generation Z, a cohort that is highly adaptive to technology yet strongly concerned with issues of security and data privacy. One innovation within the digital food service sector is the GrabFood Dine-Out Deals (DOD) feature, which integrates online voucher purchases with offline dining experiences at partner restaurants. This study aims to analyze the effect of Technology Acceptance Model (TAM) variables—Perceived Usefulness, Perceived Ease of Use, Perceived Security Risk, and Perceived Privacy Risk—on Trust toward the GrabFood Dine-Out Deals feature from the perspective of Generation Z in Indonesia. This research employed a quantitative approach using a survey method involving 300 Generation Z respondents aged 17–28 years. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results indicate that Perceived Ease of Use, Perceived Security Risk, and Perceived Privacy Risk have significant effects on Trust, while Perceived Usefulness shows a relatively weaker influence. These findings suggest that Generation Z prioritizes ease of use, security, and privacy protection over functional benefits when developing trust in digital dine-in promotional technologies.